Two centuries of Pachyrhynchus (Curculionidae, Entiminae, Pachyrhynchini) research: a comprehensive annotated checklist of taxonomy, species groups, distribution, and ecological insights in Southeast Asia - Yun Ho; Shan-Min Chen; Ace Kevin S. Amarga; Jing-Fu Tsai; Bin-Hong Ho; Ming-Luen Jeng; Hui-Yun Tseng (ZooKeys, 2025)
The genus Pachyrhynchus comprises a group of entimine weevils with diverse body coloration, endemic to the islands of Southeast Asia, with the highest diversity of species found in the Philippines. In the past ten years, many new species have been discovered, necessitating an updated list of Pachyrhynchus weevils for future study. This checklist provides the valid names, synonyms, type depository, type locality, and distribution of each Pachyrhynchus species, with ecological information such as host plants and life history. Species are further classified into defined species groups based on recent revisions using morphology and genetic analyses. A region-based analysis across eight major faunal areas highlights spatial patterns in species richness. Since the first Pachyrhynchus species was described 200 years ago, a total of 179 species and 43 subspecies (excluding nominotypical subspecies) have been recognized, with 45.8% of Pachyrhynchus species distributed in the Greater Luzon Faunal Region and 39.1% in Greater Mindanao. However, most species still lack ecological information, indicating the difficulty in collecting these data, and further investigations are needed.